Determinants of Male Circumcision for HIV/AIDS Prevention in East Central Uganda - Kironde, Brian; Wamala, Robert; Kwagala, Betty (African Journal of reproductive health, 2016)
Safe Male Circumcision (SMC) is one the effective strategies for reducing HIV transmission. The paper examines factors associated with SMC for HIV prevention, based on 4,979 males from East Central Uganda. Data were analysed using chi-squared tests and multinomial logistic regression. Older males aged 31 years and above (p < 0.001), from predominantly non-circumcising districts (Buyende - p < 0.001, Kaliro p < 0.01, and Kamuli - p < 0.01); who had neither used condoms (p = 0.03) nor tested for HIV (p < 0.001) were less likely to circumcise for HIV prevention. Males who were assessed in 2012 (p < 0.001) three years after program implementation were more likely to circumcise for HIV for HIV prevention. Males that did not take measures to prevent HIV infection were less likely to undertake SMC and are therefore highly vulnerable to infection. These (together with older males, and males from non-circumcising districts) should be targeted for promotion of SMC alongside other HIV preventive measures. For better results, the benefits SMC for children as well as adults require emphasis. Wider coverage of SMC services should entail adequate equipping of public and where feasible, private facilities and appropriate training of health personnel countrywide. (Afr J Reprod Health 2016; 20[1]: 80-87).
Keywords: Male circumcision; HIV/AIDS prevention; Uganda.